2017
DOI: 10.1002/app.46034
|View full text |Cite
|
Sign up to set email alerts
|

Novel imidazole‐grafted hybrid anion exchange membranes based on poly(2,6‐dimethyl‐1,4‐phenylene oxide) for fuel cell applications

Abstract: Novel organic-inorganic hybrid membranes, based on poly(2,6-dimethyl-1,4-phenylene oxide), have been prepared through 1,2-dimethylimidazole functional groups and double crosslinking agents including 3-glycidyloxypropyltrimethoxysilane and tetraethyl orthosilicate by sol-gel process for the purpose of improving the conductivity and alkaline resistance. The structure of membranes was characterized using Fourier-transform infrared spectra, 1 H NMR, and X-ray diffraction. The physico-chemical properties of all mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The alkane C–H stretching vibrations of methylene and methyl groups belonging to the dimethylimidazolium side chains of PBI-DIm and PBI-DIm-Si hybrid resulted in two absorption bands at 2861 cm −1 and 2940 cm −1 . Moreover, the band due to the asymmetric Si–O–Si stretching vibration usually appears in the region between 1130 cm −1 and 1030 cm −1 can be found only in the spectrum of PBI-DIm-Si hybrid [ 46 ]. This finding indicated that the hydrolysis and condensation occurred during the sol–gel process.…”
Section: Resultsmentioning
confidence: 99%
“…The alkane C–H stretching vibrations of methylene and methyl groups belonging to the dimethylimidazolium side chains of PBI-DIm and PBI-DIm-Si hybrid resulted in two absorption bands at 2861 cm −1 and 2940 cm −1 . Moreover, the band due to the asymmetric Si–O–Si stretching vibration usually appears in the region between 1130 cm −1 and 1030 cm −1 can be found only in the spectrum of PBI-DIm-Si hybrid [ 46 ]. This finding indicated that the hydrolysis and condensation occurred during the sol–gel process.…”
Section: Resultsmentioning
confidence: 99%
“…Several AEM were prepared starting from BrPPO. In Reference [ 84 ], it was quaternized with 1,2-dimethylimidazole and partially hydrolyzed to react by sol–gel with GPTMOS and TEOS were used in AEMFC. A study of the properties was conducted as a function of the inorganic content and the IEC.…”
Section: Membranes For Electrochemical Energymentioning
confidence: 99%
“…The structure showed high chemical adsorption capacities for organic water pollutants, namely Coomassie blue (CB-R250) [27]. 1,2-Dimethylimidazole was used in the preparation of another OIH material, together with poly(2,6-dimethyl-1,4-phenylene oxide, 3-GPTMS, and TEOS [28]. The matrix was developed to be applied on alkaline fuel cells, and the used precursors improved the conductivity and alkaline resistance.…”
Section: Introductionmentioning
confidence: 99%